2019
DOI: 10.2147/opth.s193751
|View full text |Cite
|
Sign up to set email alerts
|

<p>Long-term outcome of full tendon vertical rectus transposition with Foster suture in unilateral complete sixth cranial nerve palsy</p>

Abstract: PurposeTo evaluate the success rate and long-term motor and sensory outcomes of the full tendon vertical rectus transposition (VRT) with Foster suture for unilateral complete sixth cranial nerve palsy.Patients and methodsWe reviewed the medical records of patients with unilateral acquired sixth cranial nerve palsy who underwent unilateral full tendon VRT with Foster suture between 2005 and 2016 and had a follow-up of ≥2 years. Data on pre- and postoperative diplopia, face turn, ocular deviation, and limitation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The mean treatment effects at distance (60 D for DUT alone and 69 D for combined surgery) were the largest, to our knowledge, of previously reported vertical rectus transposition surgeries. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] DUT combined with maximum recession of the antagonist muscle may correct a large deviation (90 D -100 D ), as demonstrated in patients 3 and 7. As for patient 2, the ruptured muscle could have reattached to the globe and improved the duction deficit spontaneously.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The mean treatment effects at distance (60 D for DUT alone and 69 D for combined surgery) were the largest, to our knowledge, of previously reported vertical rectus transposition surgeries. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] DUT combined with maximum recession of the antagonist muscle may correct a large deviation (90 D -100 D ), as demonstrated in patients 3 and 7. As for patient 2, the ruptured muscle could have reattached to the globe and improved the duction deficit spontaneously.…”
Section: Discussionmentioning
confidence: 99%
“…23 Finally, it was reported that lateral positioning of the new insertion of the transposed tendons by posterior fixation or posterior intermuscular sutures increased the treatment effect in patients with abducens nerve palsy by augmenting the lever arm for abduction. [8][9][10][11] Similarly, DUT creates lateral positioning of the transposed tendons for approximately 5 mm at the near margin of the paralyzed muscle with the sutures anchored on the sclera adjacent to the opposite corner of the insertion. Postoperative vertical deviation is well known as a complication of vertical rectus muscle transposition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effects of Foster suture did not decline during 1–2-year follow-up, and the new path of muscle and its force remained stable. 20 41 …”
Section: R Esultsmentioning
confidence: 99%